2017
DOI: 10.3846/20294913.2016.1271061
|View full text |Cite
|
Sign up to set email alerts
|

Factors Impacting the Commercial Potential of Technologies: Expert Approach

Abstract: In order to ensure the harmonious activity of the institutions engaged in R&D and to reduce the uncertainty of the commercialization of technologies, an advanced tool for verifying decisions on technology development at early stages of commercialization, i.e. an instrument for assessing the commercial potential of technology, is needed. The article is aimed at defining the importance of factors in the commercial potential of technologies with the help of expert research. To achieve the goal, the following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 28 publications
0
36
0
Order By: Relevance
“…New technologies that are starting to emerge and dominate the world markets require constantly adapting and enhancing one's skills and qualifications Chmielewska & Horváthová 2016;Ehrenberger et al, 2015;Grenčiková et al, 2017;Hilkevics & Hilkevica, 2017, Lisin et al, 2017Radwan & Sakr, 2017;Mačerinskienė & Aleknavičiūtė, 2017;Shpak et al, 2017;Strielkowski, 2017;Żelazny & Pietrucha, 2017;Zemlickiene et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…New technologies that are starting to emerge and dominate the world markets require constantly adapting and enhancing one's skills and qualifications Chmielewska & Horváthová 2016;Ehrenberger et al, 2015;Grenčiková et al, 2017;Hilkevics & Hilkevica, 2017, Lisin et al, 2017Radwan & Sakr, 2017;Mačerinskienė & Aleknavičiūtė, 2017;Shpak et al, 2017;Strielkowski, 2017;Żelazny & Pietrucha, 2017;Zemlickiene et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, such fields of economy as agriculture, tourism, information technologies and textile industry are being invested as an alternative to the "oil needle" (Tvaronavičienė et al 2015;Zemlickiene et al 2017;Veselovsky et al 2018). With regard to this, the development of entrepreneurship which occupies an important place in social and economic policy, might be seen as a key element of the investment processes.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…They focused on Korean SMEs in IT-related businesses and found that the technology commercialization capabilities of firms mediate in the rela-tionship between R&D intensity and innovation performance. Zemlickienė, Mačiulis and Tvaronavičienė (2017) identified the main factors determining the commercial potential of technologies through a statistical analysis of the expert opinions evaluating the significance of the different factors. Their analysis is particularly relevant if implemented as basic performance guidelines during the initial stages of the technology development process.…”
Section: Complementing and Extending The Technology Diffusion Literaturementioning
confidence: 99%